THE FUTURE LANGUAGE IT TAKES OVER THE WORLD, NO ONE CAN RECOGNIZE IT AT ALL - Marufova Ruxshonaxon Kamolxon qizi; Shukhratjon Ismoiljonov (Research Focus International Scientific Journal, 2023)
The future language is a topic that explores the evolution of language in the coming years. With the rise of technology and globalization, it is expected that language will continue to change and adapt to new circumstances. Some experts predict that English will become even more dominant as a global language, while others believe that new languages will emerge as a result of cultural shifts and technological advancements. Additionally, the use of artificial intelligence and machine learning may also have an impact on language, with the possibility of creating new forms of communication and language processing. As we move towards the future, it will be interesting to see how language evolves and adapts to the changing world around us.